Speciation on the Roof of the World: Parallel Fast Evolution of Cryptic Mole Vole Species in the Pamir-Alay—Tien Shan Region - Aleksey Bogdanov; Valentina Tambovtseva; Sergey Matveevsky; Irina Bakloushinskaya (Life, 2023)
Speciation is not always accompanied by morphological changes; numerous cryptic closely related species were revealed using genetic methods. In natural populations of Ellobius tancrei (2n = 54–30) and E. alaicus (2n = 52–48) of the Pamir-Alay and Tien Shan, the chromosomal variability due to Robertsonian translocations has been revealed. Here, by comprehensive genetic analysis (karyological analyses as well as sequencing of mitochondrial genes, cytb and COI, and nuclear genes, XIST and IRBP) of E. alaicus and E. tancrei samples from the Inner Tien Shan, the Alay Valley, and the Pamir-Alay, we demonstrated fast and independent diversification of these species. We described an incompletely consistent polymorphism of the mitochondrial and nuclear markers, which arose presumably because of habitat fragmentation in the highlands, rapid karyotype changes, and hybridization of different intraspecific varieties and species. The most intriguing results are a low level of genetic distances calculated from mitochondrial and nuclear genes between some phylogenetic lines of E. tancrei and E. alaicus, as well significant species-specific chromosome variability in both species. The chromosomal rearrangements are what most clearly define species specificity and provide further diversification. The “mosaicism” and inconsistency in polymorphism patterns are evidence of rapid speciation in these mammals.